KURDISH IDENTITY AND SPORTS IN TURKEY: THE CASE OF AMEDSPOR - Irak, Dağhan (Society Register, 2018)
The Kurds, the largest minority in Turkey, have almost no visibility in Turkish sports. While Kurdish sportspeople are not discouraged from joining in sports activities, their participation is heavily monitored by the government agencies against any manifestation of ethnic identity. Football in the Kurdish regions, seen by the Turkish state as a tool to distract Kurdish youth from political activities, has always been subject to the direct intervention of the civil and military bureaucracy, their presence in club boards is not uncommon. However, a third-division club named Amedspor, challenged all the unwritten rules related to Kurds in sports, at the expense of receiving a recurring suspension from the Turkish Football Federation. This article examines the Kurdish sports and the Amedspor case through Manuel Castells’ conception of legitimizing, resistance and project identities